EXPLORING CHEMICAL CONCEPTS AND TEXTS BASED ON NATURAL SCIENCE LITERACY IN CHEMISTRY CLASSES - S.Y.Botirova (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article discusses the importance of natural science literacy in science lessons. It also provides information on creative thinking based on natural science literacy, as well as opportunities for students to understand chemistry knowledge along with new ideas and thoughts. In particular, there are questions and assignments based on creative thinking of ozone.